CEFR-aligned school-based assessment in the Malaysian primary ESL classroom - Sidhu, Gurnam Kaur; Kaur, Sarjit; Chi, Lee Jia (Indonesian Journal of Applied Linguistics, 2018)
The Malaysian ESL (English as a Second Language) curriculum has undergone several reforms since the implementation of the Malaysian Education Blueprint 2013-2025. In 2016, the Kurikulum Standard Sekolah Rendah (KSSR) or the Standard Curriculum for Primary Schools (SBCPS), first introduced in 2011, was revised to align with the Common European Framework of References (CEFR) for languages. This more action-oriented approach resulted in fundamental changes to teaching, learning, and assessment including the integration of an innovative school-based assessment (SBA). It witnessed a shift from the traditional stance of assessment of learning to assessment for learning that emphasizes both peer and self-assessment as necessary components for the development of autonomous language learners.Â  Therefore, the main aim of this study was to investigate the implementation of the CEFR-aligned SBA in the primary ESL classroom. Data were collected via a three-pronged procedure involving surveys, interviews, and document analysis from TESL (Teaching English as a Second Language) teachers in five randomly-selected schools located in Damansara, Malaysia. The findings revealed that the implementation of SBA left much to be desired and was far from formative assessment. Though teachers expressed rather positive opinions on SBA, they lacked a full understanding of the method and admitted possessing a limited knowledge of the revised CEFR-aligned ESL curriculum altogether. Teachers provided little or no constructive feedback on assignments, and learners were not encouraged to reflect on assignments. There was little evidence of peer and self-assessment required for developing autonomous learners. Teachers cited time constraints, classroom enrolment, heavy workload, and lack of training as their main challenges against the effective implementation of the CEFR-aligned SBA.